Legalization of Pre-Marriage Agreement Pandhābā from Islamic Law Perspective: (A Case Study in Bakeong Village, Sumenep) - Hosen, Hosen; Faizi, Moh. (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2020)
The pre-marriage pandhābā legalization in Bakeong Village, Guluk-Guluk, Sumenep is a procession of efforts to free a pandhābā child from bad luck and all forms of distress in his life which are carried out before the marriage ceremony procession. There are two objectives in this research; first, to find out the procession of implementing the tradition, and the second how was the view of Islamic law on the tradition. The research used a normative-qualitative approach with a type of case studies. Collecting data through unstructured interviews, non-participant observation and documentation. Data were analyzed using deductions, presentations and conclusions deductively. Data sources were from people who understood and were directly involved in the implementation, and from other records relating to the object of research. The research results were, firstly; In the pandhābā legalization procession there were several stages, such as attributes (sesajen) to be used, rasolan and khatmil Qur`ān, and bathing the pandhābā children with the water of seven wells and campoan mixed with flowers. Second; this research of Islamic law toward the tradition is not found any deviation. Even this tradition can be said to be sunnah to do, because it was full of Islamic teachings such as alms and pray together.